Impact of hypertensive disorders of pregnancy on maternal and neonatal outcomes of twin gestation: a systematic review and meta-analysis - Wu, Xiaoqing; Gu, Huifeng; Wang, Junlin (Frontiers in Pediatrics, 2023)
The impact of hypertensive disorders of pregnancy (HDP) on outcomes of twin gestations is not clear. We aimed to collate data via this meta-analysis to examine how HDP alters maternal and neonatal outcomes of twin gestations.Studies comparing pregnancy outcomes of twin gestations based on HDP and published on the databases of PubMed, CENTRAL, Scopus, Web of Science, and Embase between 1 st January 2000 to 20 th March 2023 were eligible for inclusion.Results: Twelve studies were included. A cumulative of 355,129 twin gestations were analyzed in the current meta-analysis. The pooled analysis found that the presence of HDP increases the risk of preterm birth (OR: 1.86 95% CI: 1.36, 2.55 I 2 =99%) and cesarean section in twin gestations (OR: 1.36 95% CI: 1.20, 1.54 I 2 =89%). Meta-analysis showed a significantly increased risk of low birth weight (OR: 1.30 95% CI: 1.10, 1.55 I 2 =97%), small for gestational age (OR: 1.30 95% CI: 1.09, 1.55 I 2 =96%) and neonatal intensive care unit admissions (OR:1.77 95% CI: 1.43, 2.20 I 2 =76%) with HDP in twin gestations. There was no difference in the incidence of 5-min Apgar scores <7 (OR: 1.07 95% CI: 0.87, 1.38 I 2 =79%) but a lower risk of neonatal death (OR: 0.39 95% CI: 0.25, 0.61 I 2 =62%) with HDP.HDP increases the risk of preterm birth, cesarean sections, low birth weight, SGA, and NICU admission in twin gestations. Contrastingly, the risk of neonatal death is reduced with HDP. Further studies are needed to corroborate the current results.